Foster care for adults and elderlies: Model for improvement of life quality for beneficiaries of social welfare - Rakanović-Radonjić, Andrea (Politeia, 2017)
At the Public Institution Center for Social Work Banja Luka number of requests for accommodation in a institutions of social welfare has increased, mostly from the categories of the elderly and other adults who are unable to adequately take care of themselves. This fact can be a result of growth of the older population in the total population, increase in life expectancy, increased disability and increasing the number of the oldest, over 80 years of age, due to changes in the physical and health status of people who have needs for long-term care. In addressing their demands Centre for Social Work Banja Luka chooses foster care, as much more humane, more rational and more adequate model of care than placement in an institution.